2017
DOI: 10.1021/jacs.7b01807
|View full text |Cite
|
Sign up to set email alerts
|

POMzites: A Family of Zeolitic Polyoxometalate Frameworks from a Minimal Building Block Library

Abstract: We describe why the cyclic heteropolyanion [P8W48O184]40– (abbreviated as {P8W48}) is an ideal building block for the construction of intrinsically porous framework materials by classifying and analyzing >30 coordination polymers incorporating this polyoxometalate (POM) ligand. This analysis shows that the exocyclic coordination of first-row transition metals (TMs) to {P8W48} typically yields frameworks which extend through {W–O–TM–O–W} bridges in one, two, or three dimensions. However, despite the rich struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 56 publications
0
76
0
2
Order By: Relevance
“…Kortz and co‐workers have explored the metal cation binding in the crown‐shaped [P 8 W 48 O 184 ] 40− (= {P 8 W 48 } ) and demonstrated that up to 20 Cu II ions as well as a wide range of other metal cations can be encapsulated at precise positions within the central pore (diameter ≈1 nm) of this species . The study laid the foundation for the use of {P 8 W 48 } as building block for porous frameworks: Cronin and co‐workers linked {P 8 W 48 } with metal cations (coordinated to external positions), producing a family of 3D porous frameworks with accessible pores suitable for cation uptake and release . These framework materials could conceptually bridge modular‐assembled frameworks such as metal–organic frameworks and inorganic porous materials such as zeolites.…”
Section: Inorganic Cation–pom Materials: Structure‐induced Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kortz and co‐workers have explored the metal cation binding in the crown‐shaped [P 8 W 48 O 184 ] 40− (= {P 8 W 48 } ) and demonstrated that up to 20 Cu II ions as well as a wide range of other metal cations can be encapsulated at precise positions within the central pore (diameter ≈1 nm) of this species . The study laid the foundation for the use of {P 8 W 48 } as building block for porous frameworks: Cronin and co‐workers linked {P 8 W 48 } with metal cations (coordinated to external positions), producing a family of 3D porous frameworks with accessible pores suitable for cation uptake and release . These framework materials could conceptually bridge modular‐assembled frameworks such as metal–organic frameworks and inorganic porous materials such as zeolites.…”
Section: Inorganic Cation–pom Materials: Structure‐induced Functionsmentioning
confidence: 99%
“…[82] The study laid the foundation for the use of {P 8 W 48 } as building block for porous frameworks: Cronin and co-workers linked {P 8 W 48 } with metal cations (coordinated to external positions), producing a family of 3D porous frameworks with accessible pores suitable for cation uptake and release. [83,84] These framework materials could conceptually bridge modularassembled frameworks such as metal-organic frameworks and inorganic porous materials such as zeolites. The combination of inorganic metal-oxo building units and controllable structure assembly could lead to new reactivity and applications.…”
Section: Pom Capsules As Hosts For Cationic Guestsmentioning
confidence: 99%
“…1 nm) gebunden werden können . Die Studie legte den Grundstein für die Verknüpfung von {P 8 W 48 } zu porösen Gerüsten: Cronin und Mitarbeiter verknüpften {P 8 W 48 } durch Metallkationen (koordiniert an peripheren Positionen) und erhielten eine Familie von porösen 3D‐Gerüsten mit zugänglichen Poren, die für Kationenaustausch nutzbar waren . Diese Gerüste können konzeptionell die Brücke zwischen modularen Gerüsten, wie Metall‐organischen Gerüsten, und anorganischen porösen Materialien, wie Zeolithen, bilden.…”
Section: Anorganische Kation‐pom‐materialien: Von Der Struktur Zur Fuunclassified
“…[77] Diese Gerüste mit offenen Poren zeigen eine grçßenselektive Aufnahme von kleinen Molekülen sowie Protonenleitfähigkeit und oxidationskatalytische Aktivität. [78] [83,84] Diese Gerüste kçnnen konzeptionell die Abbildung 3. Strukturdarstellung von Kation-POM-Gerüsten, beschrieben in den Abschnitten 2.2 und 2.3.…”
Section: Kationenvermittelter Aufbau Von Pom-gerüstverbindungenunclassified
“…[4] Polyoxometalatebased framework materials,o rP OMzites,a re an emerging class of configurable all-inorganic porous materials. [5] Porous materials such as zeolites or metal-organic frameworks, MOFs,a re ordered networks whose building units are linked with strong interactions via ionic,c ovalent, and coordination bonds. [6] Silver ions are often used as af lexible linkers in coordination chemistry, [7] forinstance,silver-linked molybdenum oxide POMs are very stable,b oth in the solid and liquid phases.…”
mentioning
confidence: 99%